Insight into Eu redox and Pr3+ 5d emission in KSrPO4 by VRBE scheme construction. Issue 2 (27th November 2017) - Zhou, Rongfu; Lin, Litian; Liu, Chunmeng; Dorenbos, Pieter; Tao, Ye; Huang, Yan; Liang, Hongbin
Abstract : The redox properties of Eu, the 5d energy levels of Pr 3+ and the thermal quenching characteristics of Ce 3+ and Eu 2+ luminescence are understood through the KSrPO4 structure and the VRBE scheme. Abstract : A series of Ln-doped KSrPO4 (Ln = Ce 3+, Eu 3+, Eu 2+, Pr 3+ ) phosphors are prepared through a high-temperature solid-state method. The KSrPO4 compound is confirmed to possess a β-K2 SO4 structure with the Pnma group by Rietveld refinement, and the temperature-dependent lattice parameters are investigated with the powder X-ray diffraction results at different temperatures. Ce 3+ and Eu 3+ ions are introduced to probe the crystal field strength (CFS) and the lanthanide site symmetry by using VUV-UV-vis spectroscopy. The temperature-dependent luminescence properties of KSrPO4 : Ce 3+ /Eu 2+ exhibit an excellent thermal stability of Ce 3+ /Eu 2+ luminescence. Based on the VUV-UV-vis spectra of Ce 3+ and Eu 3+ doped KSrPO4, the vacuum referred binding energy (VRBE) scheme is constructed to understand the redox properties of Eu, the 5d energy levels of Pr 3+ and the thermal quenching characteristics of Ce 3+ and Eu 2+ luminescence.